Penilaian Status Kesuburan Tanah Desa Tijayan Kecamatan Manisrenggo Kabupaten Klaten - Elvina Septianta Molle; Andre Wijaya Setiawan; Alfred Jansen Sutrisno (Agrotechnology Research Journal, 2021)
Tijayan Village is located in Manisrenggo District, Klaten Regency, which has an area of agricultural land in the form of rice fields which is 105.80 ha of 155.3 ha of the village area. The extent of agricultural land in Tijayan Village needs to be maintained to increase agricultural products ranging from rice, secondary crops, and horticulture commodities. The researcher found a lack of information about soil maintenance in Tijayan Village. Therefore, the researcher conducted this research to determine and study the soil fertility and soil management efforts based on the limiting factors of fertility in Tijayan Village. In addition, soil fertility assessment is based on a desk study, detailed survey, soil analysis, making fertility distribution maps, and descriptive analysis. Determination of soil fertility status based on Soil Research Guidelines published by Soil Research Center, Bogor Indonesia, with parameters of cation exchange capacity, base saturation, total phosphorus, total potassium, and C- organic. Map made by using the ArcGIS 10.4 application. The fertility of Tijayan Village is categorized as low soil fertility class. The limiting factors for soil fertility are soil cation exchange capacity 3.47 me/ 100 g until 12.33 me/100g, total potassium < 10 mg/100g, and C- organic 1.213% - 2.286% . Consequently, management needs to be done by adding organic matter to the soil, fertilizing organically or inorganically, and the principle of healthy plant cultivation for rice fields.